Mobile phones, gender, and female empowerment in sub-Saharan Africa: studies with African youth. Issue 1 (2nd January 2020) - Porter, Gina; Hampshire, Kate; Abane, Albert; Munthali, Alister; Robson, Elsbeth; De Lannoy, Ariane; Tanle, Augustine; Owusu, Samuel
ABSTRACT : Data from qualitative and survey research with young people in 24 locations (urban and rural) across Ghana, Malawi, and South Africa expose the complex interplay between phone ownership and usage, female empowerment, and chronic poverty in Africa. We consider gendered patterns of phone ownership and use before examining practices of use in educational settings, in business and in romantic and sexual relationships. While some reshaping of everyday routines is evident, in the specific context of female empowerment we find little support within our sites for the concept of the mobile phone as an instrument of positive transformative change. The phone's application in romantic and sexual relationships demonstrates particularly strongly the way phones are complicit in constraining women's empowerment and points to potential wider repercussions, including for educational and entrepreneurship trajectories. Women's agency is still mired within wider structures of patriarchy and chronic poverty: existing inequalities are being re-inscribed and reinforced.